Sal Regeneration: the Problem of Sal Seed and Seedling Borer Pammene theristis Meyrick in Dehra Dun Sal Forests (Lepidoptera: Eucosmidae) - Chatterjee, P. N.; Thapa, R. S. (Indian Forester, 1970)
An account of Bionomics of sal seed and seedling borer Pammene theristis Meyrick in Dehra Dun sal forests has been given in the paper.